Anatomical Study of Caudal Vertebrae of Estuary Crocodile (Crocodylus porosus), Chameleon (Bronchocela jubata) and Klarap (Draco volans) - Rosel, Aidha; Sari, Safitri Anggita Tunjung; Hasanah, Umi Uswatun (Proceeding International Conference on Science and Engineering, 2019)
Reptile tails have a unique function as self defense, autotomy, and maintaining balance while in nature. There are several species that do not have an autotomy function, these species include Estuary Crocodile (Crocodylus porosus), Java Chameleon (Bronchocela jubata), and Klarap (Draco volans). The species is a reptile class that uses its tail with different functions. Differences in function in the tail can be caused by differences in anatomical structure, morphology, and behavioral adaptations that are owned by each species. With the differences in each species, this study aims to get a comparative picture of the caudal vertebrae (coccyx) anatomy of species of estuary crocodile (Crocodylus porosus), java chameleon (Bronchocela jubata), and klarap (Draco volans) so that anatomical comparison can be seen in each species that affects the difference in tail function. The method used in this study is morphological observation with boiled method, X-Ray method, and Alizarin Red’s and Alcian Blue staining methods. Research that has been conducted shows that the anatomical structure of caudal vertebrae (coccyx) in estuary crocodile species has a larger bone structure than the bone structure of java chameleon and klarap. The anatomical structure of caudal vertebrae (coccyx) in klarap has a smaller bone structure than estuary crocodile and java chameleon. The anatomical structure of caudal vertebrae (coccyx) in java chameleon species has a longer bone structure than its body length. Caudal vertebrae of these three species do not have tail fracture fields.